CARBOHYDRATE NUTRITION AND SPORULATION OF ALLESCHERIA BOYDII - Cazin, John (1964)
Cazin, John, Jr. (University of Iowa, Iowa City), and David W. Decker. Carbohydrate nutrition and sporulation of Allescheria boydii. J. Bacteriol. 88:1624–1628. 1964.—The influence of various carbohydrates on the growth and sporulation of Allescheria boydii was studied by incorporating the test substance in a medium consisting of the inorganic salts mixture contained in Czapek Dox medium with 2% agar. The data indicate that a wide variety of carbohydrates serve adequately as the sole source of carbon for A. boydii, and for its imperfect form, Monosporium apiospermum. Of those compounds tested, only raffinose and inulin were not assimilated by any of the organisms; one strain differed from all others tested in not being able to utilize sucrose. Of the ascigerous strains tested, those maintained in stock culture for a long period of time were able to grow somewhat more profusely on the various carbohydrates; recently isolated strains produced ascocarps in greater abundance. In contrast to reports appearing in the literature, these organisms are capable of assimilating mannitol, maltose, and lactose.